Wizerunek miasta Wrocławia i Dolnego Śląska w mediach publicznych i prywatnych Saksonii - wybrane problemy - Adamczuk, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article shows the image of Wroclaw and Lower Silesia in the bordening region of the former West Germany-Saxony. The author assumes that the image is basically created by the public and private media, it evolves and it is a result of an ongoing process, but it is not a final product of it et, so it will be still changing. The author chose Saxony for his study because the informations, and because of the fact that this region borders on Lower Silesia. Both regions: Saxony and Lower Silesia officially co-operate with each other in many different spheres. In the cooperation there are a lot of common and separate steps raised by each of the areas both in regional and European scale. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 154-163